50 studies every vascular surgeon should know - Al Shakarchi, Julien, 1983- (New York, NY : Oxford University Press, 2023)
This volume presents the key studies that have shaped the practice of vascular surgery, and covers topics including carotid artery disease, aortic aneurysm, peripheral artery disease, trauma, venous disease and vascular access. Each study is concisely summarized, with an emphasis on the results and limitation of the study and its implication for practice. An illustrative clinical case concludes each review to highlight the impact of the study on clinical practice.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 23, 2023).
Keywords: Blood-vessels -- Surgery -- Case studies; Health and Wellbeing; Surgery